The Artist's Body in Performance Art - Rosa, Marta (Scenari, 2021)
The present work intends to propose an aesthetical reflection regarding the meaning and experience of the body in connection with an artistic practice characterized as an art of the body: Performance Art. Since Performance Art regards life as multiform, in order to better understand its deeper meaning and to analyse it in all its complexity, it is appropriate to partition Performance Art through the definition of specific categories (“souls” of performance). Such categories include minimalist-conceptual performance, technological performance, social-political performance and shamanic performance. In these categories, the artist’s body becomes a medium, a favoured object and ultimate aim of the artistic intervention. Through the body, the artist can wonder about the present art system and challenge the traditional idea of visual art, as well as assume an authentic philosophical role in this period, definable as “period of crisis”